Regulasi Diri Dalam Belajar Sebagai Konsekuen - Dami, Zummy Anselmus; Parikaes, Polikarpus (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2018)
The purpose of this research is to find out how the influence of parental social support against self-regulation in learning Grade VII in SMP Negeri 6 Kupang 2017/2018 school year. The research was carried out in SMP Negeri 6 Kupang located on the street Nunbaun Village Melody Delha Sub district Alak, Kupang, East Nusa Tenggara. The research method used in quantitative methods. Respondents taken in this study is 20% of all students. Thus, samples taken 20% of the 225 grade VII students are 45 students, with purposive sampling technique of wear. Data collection instruments used in this research is the question form. Data analysis techniques used in this research is the technique of simple linear regression test by doing a Test f. Results of the research there show the influence of parental social support against self-regulation in learning grade VII SMP Negeri 6 Kupang was proven by Tests performed on Î± was found to be Î± = 5%, a value F table 4.07. Thus, FcountÂ  > F table (668,888 > 4.07), then declared Ha received and H0 is rejected.